The Role of Plasma D-dimer Level Measurement to Assist Breast Cancer Histopathological Grading - Hermansyah, Dedy; Firsty, Naufal Nandita; Nasution, Rifwanul Basir; Andra, Cut Aryfa; Lubis, Anggia Chairuddin (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: The histopathological grades identification is unquestionably essential to determine the most effective approach in oncologic management, specifically in breast cancer (BC) as the most common malignancy diagnosed worldwide. Complex and micro-level alterations of coagulation function of the host may occur at some point since the reactivity of the tumor cells byproduct will dysregulate its physiologic function; as represented by the higher rate of fibrinolysis which in turn increase the D-dimer level. AIM: The study aims to provide the correlation between the level of d-dimer and histopathological grades in BC patients. METHODS: A total of 111 females with confirmed BC were included in this study, which was conducted from March to September 2021 at the teaching hospital of Universitas Sumatera Utara. After thorough clinical information analysis, the histopathological examination (HPE) was conducted to confirm the malignancy and graded based on the Bloom-Richardson grading system; therefore, the HPEs were classified into slow/moderate or poorly differentiated. The D-dimer value of >0.5 mg/L was indicated as an elevated level. RESULTS: From the 102 eligible patients to be included in the final evaluation, it was observed that 46.1% and 52.9% of the participants were presumed with elevated D-dimer level and high-grade carcinoma, respectively. The elevated D-dimer level results percentage was substantially more common in high-grade BC (72.3%, the positive predictive value analysis. Other parameters, for example, sensitivity (63.0%), specificity (72.9%), and negative predictive value (63.6%) were found to be statistically accurate (p < 0.001). CONCLUSION: The influence of tumor cells differentiation toward coagulation system or fibrin metabolism dysfunction is observable in this study. Hence, the role D-dimer level measurement should be investigated further to assist the BCs’ grading determination workup.